Local Political Policies with Shari'a Nuance in West Sumatra 2000-2018 - Nopriyasman Nopriyasman; Syafrizal Syafrizal; Oktavianus Oktavianus (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2023)
The Shari'a Regional Regulation legitimizes the implementation of Islamic cultural values and Minangkabau culture in West Sumatra. Knowledge of the reality of regional regulation practice is important for harmonizing social and state life in a pluralistic society. This research aims to explain the relationship between the emergence of the Sharia Regional Regulation in West Sumatra and its implementation in city districts in West Sumatra. This research used historical methods, namely heuristics, criticism, interpretation, and historiography. The final results of the research reveal the positive phenomenon of the implementation of Shari'a regulations in West Sumatra. The appearance of school children they dressed as Muslim. Before studying, students were accustomed to praying and memorizing several verses in the Al-Qur'an, attending a Ramadhan Islamic boarding school during the holy month of Ramadhan, and participating in Youth Wirid activities after Ramadhan. State Civil Servants (ASN) wore Muslim clothing during official hours. In certain areas, being able to read the Al-Qur’an was a condition for getting married. Regional regulations with Islamic nuances also showed the political content of the figures, social organizations and parties, legislative members (DPRD), and power politics. This study contributes to the importance of awareness and tolerance in social practices between religious communities in various community organizations and government agencies.